2015
DOI: 10.1097/igc.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Indications for 30-Day Readmission After Primary Surgery for Epithelial Ovarian Cancer

Abstract: Background To identify patients at risk for postoperative morbidities, we evaluated indications and factors associated with 30-day readmission after epithelial ovarian cancer surgery. Methods Patients undergoing primary surgery for epithelial ovarian cancer between January 2, 2003, and December 29, 2008, were evaluated. Univariable and multivariable logistic regression models were fit to identify factors associated with 30-day readmission. A parsimonious multivariable model was identified using backward and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…Besides, the complications identified were cardiopulmonary with a rate of 14.3%, infection with 11.7%, ileus with 11.1%, bleeding with 2.8%, and reoperation with 5.2%. In the study conducted by Alhilli et al, 17 it was identified that the presence of postoperative complications during the initial hospitalization increased significantly, and it was encountered 3 times more frequently with rehospitalization. In this context, the result of this study can be stated to be compliant with the studies in literature.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Besides, the complications identified were cardiopulmonary with a rate of 14.3%, infection with 11.7%, ileus with 11.1%, bleeding with 2.8%, and reoperation with 5.2%. In the study conducted by Alhilli et al, 17 it was identified that the presence of postoperative complications during the initial hospitalization increased significantly, and it was encountered 3 times more frequently with rehospitalization. In this context, the result of this study can be stated to be compliant with the studies in literature.…”
Section: Discussionmentioning
confidence: 97%
“…In a study conducted on patients with gynecological cancer by Henretta et al, 15 the population of the study was 324 women with gynecological cancer, and the rate of rehospitalization was 13.2%; in the study of Fauci et al, 16 the population for the study was 207 women with ovarian cancer who underwent surgery, and the rate of rehospitalization was 16.0%. In the study conducted by Alhilli et al, 17 where the patient population was 324 women who have epithelial ovarian cancer, the rate of rehospitalization was 19.3%. Contrary to these findings, the percentage of rehospitalization of patients was 80% in the study conducted by Jaramillo-Gonzalez et al, 18 and higher rates were also reported in other studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations